Higher lifestyle oxidative balance scores are associated with lower metabolic dysfunction-associated fatty liver disease and fibrosis risk in US adults, while dietary scores have no impact on fibrosis - Yan Chu; Nuo Cheng; Jie Feng; Yawen Cao (Archives of Medical Science, 2025)
Introduction Metabolic dysfunction related steatotic liver disease (MASLD) is a long-term liver disease. Oxidative stress plays a key role in MASLD. The oxidative balance score (OBS) measures oxidative and reactive stress, but its relationship with MASLD and fibrosis remains unclear.